"It's Our Gang" - Promoting Social Inclusion for People with Dementia by Using Digital Communication Support in a Group Activity. Issue 4 (8th August 2021) - Samuelsson, Christina; Ferm, Ulrika; Ekström, Anna
ABSTRACT: Objectives: In the present paper we aim to contribute to the understanding of how people with dementia experience using a web-based communication support application on a tablet computer in a group activity. The specific focus of the present paper is on perception of social inclusion among people with dementia in a group activity using digital communication support. Methods: The study is based on interviews with participants in a communication group for people with dementia where the application CIRCA, specifically designed to support interaction involving people with dementia, was used. Five individuals with dementia were recruited from a residential care home where they lived in different wards. Seven group interviews with the participating persons with dementia following directly after each session were carried out. Results: The views of the participants were generally very positive, regarding many aspects of the activity. In the present study, the group activity seemed more important and beneficial for the participants, than the specific use of the application in itself. Conclusions: Taking part in a group activity targeting communication made participants with dementia feel that they were part of a social group, that they had learnt things, and that they had been able to contribute with their expertise to others. Clinical Implications: Group activities targeting communication give people with dementia the opportunity to exercise their social inclusion practices. Group activities may render a feeling of social community and a sense of belonging to the participants. The use of digital communication support may enhance such activities.